TREATMENT IN FREEDOM: POINTS OF TENSIONING AND ADVANCE IN A PSYCHOSOCIAL CARE CENTER - Ariane da Cruz Guedes; Luciane Prado Kantorski; Valéria Cristina Christello Coimbra; Agnes Olschowsky; Jandro Moraes Cortes; Karen Jeanne Cantarelli (Universidade Federal de Santa Maria, 2014)
http://dx.doi.org/10.5902/217976928931 Aim: knowing the tensioning and advances of the treatment in freedom in a Psychosocial Attention Center (PAC), under the vision of the users of the service. Method: exploratory and descriptive study, with qualitative methodological approach, an extract from the research Evaluation of the PAC in the South of Brazil. The data collection was developed by three researchers in one PACII in the city Alegrete-RS, in the second semester of 2006. Semi-structured interviews were done with 11 users. Results: four themes were identified: advance in the treatment with freedom; the strategies for social reinsertion; the user's repositioning as citizen and the critical knots of the treatment in freedom. Final considerations: through the participants, it is perceived that PAC invests in strategies that promote the social reinsertion of the users, which contributes significantly so that the treatment in mental health is with freedom, strenghtening the repositioning of the user as citizen.